Big Bubble Deep Anterior Lamellar Keratoplasty for Management of Deep Fungal Keratitis. (1st July 2014) - Gao, Hua; Song, Peng; Echegaray, Jose J.; Jia, Yanni; Li, Suxia; Du, Man; Perez, Victor L.; Shi, Weiyun
Abstract : Objective . To evaluate the therapeutic effect of big bubble deep anterior lamellar keratoplasty (DALK) in patients with deep fungal keratitis. Methods .   Consecutive patients who had DALK for deep fungal keratitis at Shandong Eye Hospital between July 2011 and December 2012 were included. In all patients, the infiltration depth was more than 4/5ths of the corneal thickness. DALK surgery was performed with bare Descemet membrane (DM) using the big bubble technique. Corrected distance visual acuity (CDVA), graft status, and intraoperative and postoperative complications were monitored. Results . Big bubble DALK was performed in 23 patients (23 eyes). Intraoperative perforation of the DM occurred in two eyes (8.7%) during stromal dissection. The patients received lamellar keratoplasty with an air bubble injected into the anterior chamber. Double anterior chamber formed in 3 eyes (13.0%). Mean CDVA of the patients without cataract, amblyopia, and fungal recurrence was improved from preoperative HM/20 cm−1.0 (LogMAR) to 0.23   ±   0.13 (LogMAR) at the last followup (P < 0.01 ). Fungal recurrence was found in two patients (8.7%). Corneal stromal graft rejection was noted in one patient (4.3%). Conclusions . DALK using the big bubble technique seems to be effective and safe in the treatment of deep fungal keratitis unresponsive to medication.